Deep RRT* - Dang, Xuzhe; Chrpa, Lukáš; Edelkamp, Stefan (Proceedings of the International Symposium on Combinatorial Search, 2022)
Sampling-based motion planning algorithms such as Rapidly exploring Random Trees (RRTs) have been used in robotic applications for a long time. In this paper, we propose a method that combines deep learning with RRT* method. We use a neural network to learn a sample strategy for RRT*.We evaluate Deep RRT* in a collection of 2D scenarios. The results demonstrate that our algorithm could find collision-free paths efficiently and fast, and can be generalized to unseen environments.